Emotional Intelligence As a Significant Tool in IT Industry - Gupta, Bhavna (Journal of Commerce and Trade, 2018)
Emotional Intelligence (EI) has attracted increasing attention and enjoyed a robust resurgence across a wide range of disciplines of psychology, education, and human resources over the last decade. The present decade has seen an ongoing interest of professionals and academicians toward the value of emotions at workplace. Tall claims have been made on one hand, while, on the other hand, the validity of such claims have been severely questioned Classification-JEL : O33, O34